2014
DOI: 10.1371/journal.pone.0087616
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of Migraine-Related Genes in Different Tissues of the Rat

Abstract: 17ß-Estradiol, an epigenetic modulator, is involved in the increased prevalence of migraine in women. Together with the prophylactic efficacy of valproate, which influences DNA methylation and histone modification, this points to the involvement of epigenetic mechanisms. Epigenetic studies are often performed on leukocytes, but it is unclear to what extent methylation is similar in other tissues. Therefore, we investigated methylation of migraine-related genes that might be epigenetically regulated (CGRP-ergic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…The non-parametric Mann–Whitney test was performed to evaluated group differences with regard to DNA methylation level. Since the CpG sites within RAMP1 gene promoter region are not independent but correlated with each other [ 17 ], and the sample size was small, we did not perform the strict Bonferroni correction or other conservative approach. The receiver operating characteristic (ROC) curve and Youden criterion were used to determine the optimal cut-off point of methylation level.…”
Section: Methodsmentioning
confidence: 99%
“…The non-parametric Mann–Whitney test was performed to evaluated group differences with regard to DNA methylation level. Since the CpG sites within RAMP1 gene promoter region are not independent but correlated with each other [ 17 ], and the sample size was small, we did not perform the strict Bonferroni correction or other conservative approach. The receiver operating characteristic (ROC) curve and Youden criterion were used to determine the optimal cut-off point of methylation level.…”
Section: Methodsmentioning
confidence: 99%
“…DNA methylation patterns of genes associated with migraine pathophysiology that are likely epigenetically regulated, including genes for CALCA, RAMP1, CRCP, and CALCRL, were compared in various tissues. For previously studied genes coding for CALCA and RAMP1, methylation pattern concordance was observed among all tissues, thus demonstrating that CALCA and RAMP1 gene results could be extrapolated to neurological tissue [130]; however, this result was not observed for the other two genes. Meanwhile, the authors observed high agreement between DNA methylation in rat and human leukocytes [130], indicating that it is possible to study DNA methylation in rat tissues for tissues or samples that would be difficult to obtain from humans.…”
Section: Environmental Factors and Migrainementioning
confidence: 73%
“…For previously studied genes coding for CALCA and RAMP1, methylation pattern concordance was observed among all tissues, thus demonstrating that CALCA and RAMP1 gene results could be extrapolated to neurological tissue [130]; however, this result was not observed for the other two genes. Meanwhile, the authors observed high agreement between DNA methylation in rat and human leukocytes [130], indicating that it is possible to study DNA methylation in rat tissues for tissues or samples that would be difficult to obtain from humans. In contrast, several genes encoding proteins involved in the methylation cycle, such as the methylene tetrahydrofolate reductase gene (MTHFR), have not been associated with migraine using GWAS.…”
Section: Environmental Factors and Migrainementioning
confidence: 73%
See 2 more Smart Citations